Postoperative abnormal response of C-reactive protein as an indicator for infectious complications after oral oncologic surgery with primary reconstruction - Akashi, Masaya (J Otolaryngol Head Neck Surg, 2015)
BACKGROUND: C-reactive protein (CRP) screening has been reported to be reliable for detection of infectious complications. Postoperative abnormal response of CRP can predict wound infection in colorectal surgery. This study aimed to determine the efficacy of CRP monitoring to detect infectious complications in oral oncologic surgery. METHODS: One hundred patients who underwent oral cancer resection with primary reconstruction were enrolled. Postoperative kinetics of CRP were classified into a normal or abnormal response. RESULTS: A normal CRP response after surgery was observed in 61 patients and an abnormal response was observed in 39. There were postoperative infectious complications in 21 patients, with surgical site infections in 13 patients (early onset in six and late onset in seven). Non-wound infections were found in nine patients. Sensitivity, specificity, the positive predictive value, and the negative predictive value for abnormal CRP response as a predictor for early infectious complications were 100%, 70.1%, 35.9%, and 100%, respectively. CONCLUSION: Postoperative serial CRP screening is a useful test as an indicator of infectious complications in oral oncologic surgery. Normal CRP responses can rule out almost all early infectious complications.